THE EFFECT OF CORE COMPETENCIES, TRANSFORMATIONAL LEADERSHIP AND JOB SATISFACTION ON PERFORMANCE MODERATED BY WORK ENVIRONMENT IN - Rahayu Lestari, Melati; Rachmat, Basuki; Prawitowati, Tjahjani; Yulianti, Emma (JURNAL EKBIS, 2024)
Post Covid-19 Pandemic, PT Wings Surya Surabaya Wonocolo District still applies operational work standards during the pandemic. The quality and quantity of core competencies have certainly changed employees. This study examines: (1) the influence of core competencies and leadership styleon job satisfaction at PT Wings Surya Surabaya Wonocolo District. (2) The influence of core competencies and leadership style on employee performance at PT Wings Surya Surabaya Wonocolo District. (3) The influence of job satisfaction on employee performance which is strengthened by the work environment at PT Wings Surya Surabaya Wonocolo District. The research method used is descriptive analysis using the Likert scale as a questionnaire measuring tool and the help of the War-PLS7.0 data processing application. The results of the study show (1) core competencies and leadership styles have a significant effect on performance and performance, (2) through job satisfaction, core competency styles do not have an effect on performance, (3) the work environment is unable to moderate satisfaction with performance. The implications of the research that emerge are the success of active and transformative leaders in the company and the attitudes and character of each employee's competence are able to influence performance and job satisfaction for the better, but a comfortable, safe and clean work environment is still unable to be a factor that strengthens employee satisfaction to improve performance.